Student perceptions of online biology learning during the COVID-19 pandemic - Musyeri, Novela Ivany; Nebore, Idola Dian Yoku; Nunaki, Jan Hendriek (Univeritas Papua, 2022)
This study aims to determine students' perceptions of the online biology learning process in class X IPA 1 SMA Negeri 1 Manokwari. This type of research uses a survey method. This study's data collection techniques used a questionnaire instrument and data analysis techniques using percentages. The population in this study amounted to 35 students of class X IPA 1 SMA Negeri 1 Manokwari by using the saturated sampling technique so that the determination of the number of samples is that all members of the population are sampled. Based on overall learning outcomes with an average indicator value of 64.43%, it was concluded that students' perceptions of the online biology learning process in class X IPA 1 SMA Negeri 1 Manokwari were in the passable category.